Circulating t-PA antigen predicts major adverse coronary events in patients with stable coronary artery disease – a 13-year follow-up - Niessner, Alexander; Graf, Senta; Nikfardjam, Mariam; Speidl, Walter S.; Huber-Beckmann, Renate; Zorn, Gerlinde; Wojta, Johann; Huber, Kurt (Thrombosis and Haemostasis, 2003)
Thrombus formation after rupture of an atherosclerotic plaque plays a crucial role in coronary artery disease (CAD). A decreased endogenous fibrinolytic system and prothrombotic factors are supposed to influence coronary thrombosis. It was our aim to investigate the predictive value of tissue plasmino-gen activator (t-PA) antigen, von Willebrand Factor, Lipoprotein (a) and anti-cardiolipin antibodies for major adverse coronary events in patients with stable CAD in a prospective cohort study of more than 10 years.We observed 141 patients with angiographically proven CAD for a median follow-up period of 13 years. t-PA antigen was the only marker predicting coronary events (logistic regression, p = 0.044) with a poor prognosis for patients in the 5th quintile with an odds ratio of 7.3 (compared to the 1st quintile). The odds ratio even increased to 10.0 for coronary events associated with the “natural course” of CAD excluding events due to restenosis. t-PA antigen had a slightly higher prognostic power (ROC curve; AUC = 0.69) than fasting glucose (AUC = 0.68) and cholesterol (AUC = 0.67). Triglycerides influenced plasma levels of t-PA antigen (regression, p < 0.001). The predictive value of t-PA antigen remained significant after adjustment for inflammation (logistic regression, p = 0.013) and extent of CAD (p = 0.045) but disappeared adjusting for insulin resistance (p = 0.12).In conclusion t-PA antigen predicted coronary events during a very long-term follow-up with a comparable prognostic power to established cardiovascular risk factors. Markers of insulin resistance influenced t-PA antigen and its predictive value.Part of this paper was originally presented at the joint meetings of the 16th International Congress of the International Society of Fibrinolysis and Proteolysis (ISFP) and the 17th International Fibrinogen Workshop of the International Fibrinogen Research Society (IFRS) held in Munich, Germany, September 2002.
Keywords: Tissue plasminogen activator; endogenous fibrinolytic system; coronary artery disease; long-term follow-up; prospective cohort study